Do Cross-National Differences in the Costs of Children Generate Cross-National Differences in Fertility Rates? - Hana Pacalova; Henriette Engelhardt; S. Philip Morgan; Thomas A. DiPrete (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
Parity-specific probabilities of having a next birth are estimated from national fertility data and are compared with nation-specific costs of having children as measured by time-budget data, by attitude data from the International Social Survey Program, and by panel data on labor earnings and standard of living changes following a birth. We focus on five countries (the US, West Germany, Denmark, Italy, and the United Kingdom), whose fertility rates span the observed fertility range in the contemporary industrialized world and whose social welfare and family policies span the conceptual space of standard welfare-state typologies. Definitive conclusions are difficult because of the multiple dimensions on which child costs can be measured, the possibility that child costs affect both the quantum and the tempo of fertility, the relatively small fertility differences across industrialized nations, and the inherent small-N problem resulting from nation-level comparisons. Empirical analysis, however, supports the assertion that institutionally driven child costs affect the fertility patterns of industrialized nations.
Keywords: 330; Fruchtbarkeit; Kinder; Kosten; Zeitbudgetforschung; Familienleistungsausgleich; Vergleich; Vereinigte Staaten; Deutschland; Dänemark; Italien; Grossbritannien